ARTISTIC AND POETIC LANGUAGE FEATURES IN HAZINIY’S WORKS - Hayitov M. T. (Modern American Journals, 2025)
Haziniy is regarded as one of the representatives of classical Uzbek literature whose poetic language embodies a rich synthesis of cultural heritage, spiritual symbolism and artistic mastery. His works demonstrate a refined command of both colloquial and elevated literary diction, forming a distinct poetic atmosphere grounded in Oriental mystical aesthetics. The artistic language of Haziniy is marked by the frequent use of symbolic metaphors, allegorical expressions, Quranic and Hadith allusions, folkloric imagery and emotional lyricism which together construct a multilayered semantic structure. The lyrical tone of his poetry reflects emotional sincerity, spiritual longing, philosophical contemplation and subtle moral reflection. The interaction of rhythm, sound harmony and semantic depth in his verses highlights his ability to convert inner spiritual experience into aesthetically powerful expression. This research explores the artistic and poetic language features in Haziniy’s works by analyzing his lexical choices, figurative style, imagery and individual authorial voice. Special attention is given to how the poet employs traditional literary devices while preserving originality, and how his linguistic creativity contributes to the emotional impact and philosophical sophistication of his poetry.
Keywords: Haziniy, poetic language, classical literature, imagery, metaphor, symbolism, mystical aesthetics, lyrical expression.